UMPSAs Friendly Golf with agencies and industries strengthens relationships - Mimi Rabita, Abd Wahit (UMPSA, 2023)
KUANTAN, 29 October 2023 - A total of 80 individuals participated in the UMPSA Friendly Golf programme with the Industry in conjunction with the branding of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and the 21st Anniversary of UMPSA held recently at the Royal Pahang Golf Club.